2014
DOI: 10.1111/jocs.12448
|View full text |Cite
|
Sign up to set email alerts
|

A Metaanalysis and Systematic Review of Wrapping of the Ascending Aorta

Abstract: The results of the metaanalysis suggest that external aortic wrapping may be considered as a safe operative technique. In patients with a moderately dilated aorta it offers good mid-term and long-term outcome compared to replacement of the ascending aorta.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 23 publications
(127 reference statements)
1
44
0
2
Order By: Relevance
“…In a more recent study, Zhang et al found that the use of blood products and the duration of postoperative hospital stay were also lower in patients who underwent wrapping than in those who underwent AA replacement (33). These findings have been confirmed in a recent meta-analysis of five studies that compare the results of wrapping and RAA (30). On the contrary, Lee et al did not find differences regarding mortality or the incidence of major postoperative complications between both techniques (9).…”
Section: Early Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…In a more recent study, Zhang et al found that the use of blood products and the duration of postoperative hospital stay were also lower in patients who underwent wrapping than in those who underwent AA replacement (33). These findings have been confirmed in a recent meta-analysis of five studies that compare the results of wrapping and RAA (30). On the contrary, Lee et al did not find differences regarding mortality or the incidence of major postoperative complications between both techniques (9).…”
Section: Early Resultsmentioning
confidence: 92%
“…Hospital mortality in the more than 700 patients included in the meta-analysis by Plonek was only 1.5%, and the deaths were unrelated to the surgical technique (30). No mortality was recorded on patients who underwent isolated wrapping or wrapping associated with AA plication, whereas it increased to 2% in patients who underwent concomitant aortoplasty with resection of the aortic wall.…”
Section: Early Resultsmentioning
confidence: 97%
See 3 more Smart Citations